(untitled) (Human Factors in Design, 2021)
With smaller screens, icons without labels are, on mobile devices, the main form of interaction. There was a need to verify that these icons are easily recognized by their target audience. The problem raised in this research is the lack of standardization of icons for use in these devices. The objective was to verify if widely used icons are easy to recognize, so that they can be used without a label. Tests with interfaces were carried out, using methods such as eye tracking and questionnaire application. The results showed that, in some situations, the use of labels in the icons can delay or difficult the interaction, from the point of view of Universal Design. In addition, widely used icons proved to be easily recognized, which justifies the removal of the labels of the icons.